Scripting middle east leaders : the impact of leadership perceptions on U.S. and uk foreign policy - Freedman, Sir Lawrence; Michaels, Jeffrey ([S.l.] : Bloomsbury Academic, 2012)
Both the US and the UK seemed caught off-guard by the uprisings in Libya and Egypt and policymakers had to deal with leaders that switched from being allies to "pariahs." This collection of essays, written by leading scholars, examines the evolution of British and American perceptions of "adversaries" in the Middle East since the Cold War. It traces the evolution of how leaders have been perceived, what determined such perceptions, and how they can change over time. It shows that in many cases the beliefs held by policymakers have influenced their policies and the way they adapted during crisis. Each essay focuses on a Middle East leader, such as Nasser, Assad, Hussein, or Ahmadinejad, discussing what these leaders' objectives were perceived to be, the assessments of their willingness to take risks or negotiate, and how such assessments changed overtime and were evaluated in retrospect. This groundbreaking contribution to the literature on leadership attitudes and perceptions in policymaking toward the Middle East will appeal to anyone studying foreign policy, Middle East politics and political psychology.
Keywords: Great Britain; International relations; Leadership; Middle East; Political science; United States